Discrimination by Western Society Forming A Self-Actualization on Afaf in ’The Beauty of Your Face’ - Airis Adrian Dinata; Nabil Mahendra (Morphosis: Journal of Literature, 2024)
The purpose of this research is to study the fate of women in western society who always get discrimination of it, regardless of her personal life matter, especially if she’s from the middle-east and specifically to those who stand behind Islam religion and try to blend in. The discrimination above had wrapped perfectly in the novel The Beauty of Your Face by Sahar Mustafah. The method of research that would be used is qualitative. Whereas the theory that would be used is feminist theory: Self-actualization by Abraham Maslow. The end result of this research would be the discussion of how the main character found her way to become a muslim who eventually could handle all of her obstacles either in personal life or as muslim women in western society. Keywords: Western society, middle-east, Islam, Discrimination, Self-actualization